The incidence of Anxiety and Depression in Patients with Spinal Injury at Siriraj Spinal Unit - Chavasiri, MD, Srinual; Sukprasert, MA, Nopchanok; Chavasiri, MD, Cholavech (Journal of Southeast Asian Orthopaedics, 2022)
Objective: To investigate the incidence of anxiety and depression among patients with spinal injury admitted to the Siriraj Spinal Unit, and to compare depression and anxiety scores between admission and discharge. We also evaluated for factors that significantly associate with unimproved anxiety and depression score. Methods: This prospective study included patients with spinal injury that were admitted to the Siriraj Spinal Unit of Siriraj Hospital during December 2013 to August 2017. Presence and level of anxiety and depression were assessed using Thai Hospital Anxiety and Depression Scale (Thai HADS). The following data were collected: age, gender, education level, marital status, occupation, diagnosis, level of impairment, injury severity, cause of injury, and length of stay. Results: Ninety patients were included, with a mean age of 44.4±16.7 years. There were 68.9% males and 31.1% females. The incidence of anxiety and depression on the day of admission was 8.9% and 7.8%, respectively, with decreases to 4.4% and 5.6% before discharge (Table 2). Mean HADS score for anxiety decreased from 6.1±3.2 to 3.2±2.9, and for depression from 5.1±3.4 to 3.0±3.1. In multivariate analysis, age and marital status were significantly associated with unimproved depression score (P=0.003 and P=0.025, respectively). No evaluated factors were significantly associated with unimproved anxiety score. Conclusion: The incidence of anxiety and depression decreased from 8.6% and 7.8% to 4.4% and 5.6%, respectively, compared between admission and discharge. Age and marital status were significantly associated with unimproved depression score, while no factors were able to significantly predict unimproved anxiety score.